Baabus Shiaam's Poetry as a Media for Education in Religious Values - Hanan; Moh. Ahsan Shohifur Rizal (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
Oral literature is a type of literary work produced by society based on a creative process, in which the values ​​and norms of life are conveyed orally, using language as the medium. Poetry is one of the oral literary works that is currently less popular with the public, especially the younger generation. This happens because they just read without delving into the meaning of the poetry, so that the true purpose and meaning are not conveyed to the reader. In fact, if understood in depth, poetry is not only a literary work that functions as entertainment, but poetry can also function as an educational medium. One of them is the poem Baabus Shiaam, this poem not only contains aesthetic values, but also contains religious values ​​in it. This research aims to review the actual meaning and role of Baabus Shiaam poetry, especially in teaching Islamic religious values. The method used in this research is a descriptive qualitative method. Interview techniques, recording, documentation, transcription, and transliteration are all used in data collection methods. The results of this research are that the poetry of Baabus Shiaam has the aim of creating something related to people's lives, namely helping people recognize and remember things related to fasting. Apart from that, the poet also teaches religious values ​​through this poetry. So, it can be concluded that Baabus Shiaam's poetry has a very important role, namely functioning as a medium for education and teaching Islamic religious values ​​to society.